The Relationship Between Kirsten Rat Sarcoma Mutations and Mismatch Repair Status in Colorectal Cancer Patients: A Preliminary Study - Sulfikar, Sulfikar; Warsinggih, Warsinggih; Kusuma, Muhammad Ihwan; Bahar, Burhanuddin; Arsyad, Arham; Faruk, Muhammad (Asian Pacific Journal of Cancer Biology, 2025)
Background: Chromosomal instability (CIN) is a key pathway in colorectal cancer (CRC) tumorigenesis, occurring in 80%-85% of cases and leading to aneuploidy. CIN tumors often harbor mutations in APC, KRAS, and TP53, which drive tumor progression. Another crucial pathway, microsatellite instability (MSI), results from DNA mismatch repair (MMR) defects, leading to a hypermutable phenotype. MSI-CRC has distinct clinicopathologic features and a better prognosis than proficient MMR (pMMR) CRC. KRAS mutations, found in approximately 40% of CRC cases, drive tumor progression via the RAS/RAF/MAPK pathway. This study investigates the relationship between KRAS mutations and MMR status in CRC patients. Methods: A preliminary cross-sectional study was conducted on CRC patients. KRAS mutations were analyzed using PCR, while MMR status was determined via immunohistochemistry and microsatellite testing. Clinical variables, including cancer stage, tumor category, and location, were analyzed. Results: Among 55 patients, 91.3% had pMMR and 8.7% had deficient MMR (dMMR). KRAS mutations were more frequent in pMMR patients (80% of cases). Patients with pMMR and KRAS mutations exhibited aggressive tumors but responded to conventional therapy, whereas dMMR patients with KRAS mutations showed complex molecular profiles, potentially benefiting from immunotherapy. Conclusion: KRAS mutations are primarily associated with pMMR in CRC, indicating distinct molecular pathways. Personalized treatment strategies should consider MMR status and KRAS mutations to optimize therapeutic outcomes. Further research is needed to explore their clinical implications.